PERBEDAN KINERJA PEGAWAI DENGAN PERJANJIAN KERJA WAKTU TIDAK TERTENTU DAN PERJANJIAN KERJA WAKTU TERTENTU DI FEB UNSRATMANADO - Pingkan Rorong; Rita N. Taroreh; Imelda. W. J. Ogi (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
Humans are the most important resource in an organization. At work, each employee is a unique individual because he has different thoughts and behaviors, which results in differences in his performance. For that, a plan, organization, direction and supervision of employee performance is needed which is usually called Performance Management. Research objects are employees at FEB UNSRAT. This study uses a comparative method. The data collection techniques used were questionnaires and observations. The total population of the unsrat FEB is 74 people. Sampling of this research was determined using purposive sampling technique of 27 people, each 13 permanent employees and 14 non-permanent employees. The data analysis method used the t-test (independent sample t-test). The results showed that there was a significant difference between the performance of permanent employees and non-permanent employees at FEB UNSRAT. Kata kunci: kinerja, pegawai tetap, pegawai tidak tetap.